MOLECULAR DOCKING, MOLECULAR DYNAMICS, AND IN SILICO TOXICITY PREDICTION STUDIES OF COUMARIN, N-OXALYLGLYCINE, ORGANOSELENIUM, ORGANOSULFUR, AND PYRIDINE DERIVATIVES AS HISTONE LYSINE DEMETHYLASE INHIBITORS - Muttaqin, Fauzan Zein; Fakih, Taufik Muhammad; Muhammad, Hubbi Nashrullah (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Prostate cancer is the second most common cancer in men. One of the efforts in the treatment of prostate cancer is by inhibiting histone lysine demethylase. Derivative compounds of coumarine, N-oxalylglycine, organoselenium, organosulfur, and pyridine have been reported to be active against two types of histone lysine demethylase (KDM) enzymes, KDM4E and KDM5B. This study aims to study the interactions of these derivatives with KDM. Methods: In this study, we performed computational studies, including molecular docking and molecular dynamics (MDs) simulations, and toxicity prediction, to assess the compounds' activities toward three other KDM enzymes, KDM1A, KDM4A, and KDM4C. Results: Molecular docking simulations showed that a derivative compound of N-oxalylglycine, (R)-3-(4-[benzyloxy]phenyl)-2-(carboxyformamido) propanoic acid, and a derivative compound of pyridine, 3-(4-methoxybenzylamino)pyridine-2,4-dicarboxylic acid, has the highest affinity toward KDM. These results were confirmed in MDs studies which showed strong interactions at the active site of the five receptors. Toxicity prediction results show that the derivative compounds of coumarine, N-oxalylglycine, organoselenium, organosulfur, and pyridine are classified in category (high class), which suggests that the safety is not guaranteed, but is likely, not carcinogenic and nongenotoxic. Conclusion: Several coumarin, N-oxalylglycine, organoselenium, organosulfur, and pyridine derivative compounds are predicted to be able to interact strongly with KDM. The results in this study are useful for further studies in the development of novel anticancer drugs that target KDM.